Human Papilloma Virus Vaccination Acceptance of Elementary School Student’s Parents (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
A costless vaccination program had been implemented in Badung Regency, but there were parents of elementary schoolgirls who did not give written consents to their daughters for joining the program. The research intended to determine the factors of HPV vaccination program acceptability comprised of age, education level, knowledge, perception, and doctor recommendation. The research design was quantitative-based cross-sectional from January – May 2020. The population study was elementary schoolgirls’ parents in Badung Regency. The respondents were 92 parents who were selected based on two strata and using simple random sampling. The source of primary data was collected through interviews and online questionnaires. It was analyzed with descriptive and analytical techniques with a logistic regression test. The result showed that 64,13% of respondents accepted the HPV vaccination program. The multivariate analysis showed that the perceived barrier was the most influential factor towards the acceptability of the HPV vaccination program (AOR = 6,056; 95%CI 1,754-20,906). Education would be needed to decrease the barriers to the HPV vaccination program.